Assimilating Quality Function Deployment (QFD) with QUEST® Analysis for Facility Layout Redesign of Handwork Section - Isa, Halim (2010)
Quality function deployment (QFD) is a powerful customer-oriented tool to facilitate the customer needs. In this paper, an attempt has been made to examine the applicability of Quality Function Deployment (QFD) as a suitable design management tool for improving facility layout design of small and medium manufacturing industries. For this purpose, a simple case study using QFD has been conducted where survey has been done to collect and verify the expectations of the customer/worker profile for designing the facility layout. This paper presents the integration between QFD approaches with simulation modelling within a facility layout of a Handwork Section; Miyazu (M) Sdn Bhd, located in Shah Alam, Selangor. The department is struggling to locate the incoming parts from the depot since the pickup and drop off buffer is not properly placed, which results to untidy appearance. Quest simulation analysis is found to be very powerful tool that can be used in the design phase. Simulation modelling activity is used in this study since it allows verification of the floor design without having to rearrange the actual physical layout. The case study findings demonstrated that QFD approach is possible to prioritize and implement the new layout solutions at the onset of the design stage before the actual layout implementation.